Theory of paradeterminants and its applications - Zatorsky, R.A. (Algebra and Discrete Mathematics, 2007)
We consider elements of linear algebra based on triangular tables with entries in some number field and their functions, analogical to the classical notions of a matrix, determinant and permanent. Some properties are investigated and applications in various areas of mathematics are given.